A case of Graves’ disease developing with exacerbation of sarcoidosis - Makino, Shinya; Chisako, Yagi; Mariko, Naka; Sachie, Hirose; Masayoshi, Fujiwara; Chiho, Ohbayashi (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2019)
A 53-year old female was referred to our hospital with bilateral abnormal shadow in the chest X-ray. Computed tomography revealed multifocal ill-defined densities and thickening of bronchial wall and pulmonary vessels by fine nodules combined with massive enlargement of bilateral mediastinal and hilar lymph nodes. Analyses of bronchoalveolar lavage fluid and transbronchial lung biopsy specimen showed the increase in CD4/CD8 ratio and the presence of non-caseating granulomas, respectively. In addition, serum angiotensin-converting enzyme was extremely high, leading to the diagnosis of sarcoidosis. Simultaneously, she complained of palpitation and sweating. Endocrinological examination showed comorbid hyperthyroidism without anti-TSH receptor antibody (TRAb). In the first 2-3 months, pulmonary shadow gradually disappeared without steroid administration. In parallel, serum thyroid hormone levels were gradually normalized in the beginning, but increased after 3 months with an appearance of TRAb. After initiation of treatment with antithyroid agent, hyperthyroidism was improved within 9 months, and changed into hypothyroidism thereafter. The clinical course of this rare case suggest that immunological storm by exacerbation of sarcoidosis may trigger the onset of autoimmune thyroid disease, in which hyperthyroidism with stimulating type of TRAb subsequently changed into hypothyroidism with blocking-type TRAb.